DOI: 10.11606/t.5.2010.tde-03112010-163716
|View full text |Cite
|
Sign up to set email alerts
|

Custos hospitalares da meningite causada por Streptococcus pneumoniae na cidade de São José dos Campos, SP

Abstract: À minha orientadora, Profa. Dra. Ana Maria de Ulhôa Escobar, com todo o meu respeito, admiração e gratidão por toda a confiança em mim depositada, fundamentais para a conclusão desta tese, e também por todo incentivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…A gap is perceived due to the lack of updating of these values, a situation also demonstrated in a study on the costs of hospital treatment for pneumococcal meningitis in São José dos Campos, state of São Paulo, which showed that costs were ten to twenty times higher than the average paid by SUS. 18 It is noteworthy the fact that, in this study, some items are not accounted for and that indirect costs were not included. The IHA values paid by SUS do not reflect the actual costs of treating CS and do not follow inflationary indices such as the Broad National Consumer Price Index (IPCA, Índice Nacional de Preços ao Consumidor Amplo) and the National Consumer Price Index (INPC, Índice Nacional de Preços ao Consumidor).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A gap is perceived due to the lack of updating of these values, a situation also demonstrated in a study on the costs of hospital treatment for pneumococcal meningitis in São José dos Campos, state of São Paulo, which showed that costs were ten to twenty times higher than the average paid by SUS. 18 It is noteworthy the fact that, in this study, some items are not accounted for and that indirect costs were not included. The IHA values paid by SUS do not reflect the actual costs of treating CS and do not follow inflationary indices such as the Broad National Consumer Price Index (IPCA, Índice Nacional de Preços ao Consumidor Amplo) and the National Consumer Price Index (INPC, Índice Nacional de Preços ao Consumidor).…”
Section: Discussionmentioning
confidence: 98%
“…In 2008, the Table of Procedures, Medicines, Orthotics, Prosthetics and Special Materials (SIGTAP -Portuguese acronym) was established to create the SUS and Ambulatory (SIA) and Hospital (SIH) Information System databases; however, even after these values were readjusted, resources from SUS are still scarce and limited. 18 When the child needs a neonatal ICU bed, it is possible to increase the values, as well as the costs of more complex tests. Nonetheless, it is still likely that these costs are underestimated, not characterizing the costs adequately, consisting of reimbursed amounts and not the actual values of the health resources that were used, as it may have been necessary to perform additional procedures that were not foreseen in the list of those covered by the IHA and,therefore,they were not computed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation